The response of the natural and sewage-impacted intertidal mussel community of the SW Atlantic to pulse (before / after summer) and chronic sewage discharges in the 1997 - 2014 period - Elias, Rodolfo (2022)
Until 2014 Mar del Plata city discharged its untreated sewage effluents to the intertidal sector. This city has a marked seasonality in the urban discharge, varying between 2.8 and 3.5 m3 s-1 of effluents before/after summer. The effect on the intertidal benthic community was evaluated in both spatially, in sewage-impacted and reference sites, and temporarily in both the short term, before/after summer, and in long term along nine periods between 1997-2014. The bivalve Brachidontes rodriguezii, the ecosystem engineer, reach the maximum dominance and frequency in reference areas. Spatially the presence of opportunistic and tolerant species characterized the impacted areas, while in reference sites sensitive species were prevalent. The opportunistic polychaete species Capitella ‘capitata’ sp. and Alitta succinea were dominant near the sewage discharge in firsts periods. In other periods the indicator species were Rhynchospio glutaea or Boccardia spp. From 2008 the invader Boccardia proboscidea characterized the sewage-impacted sites building massive reefs. The crustaceans Jassa falcata and Caprella sp. were very abundant at intermediate distances from the sewage discharge, while Monocorophium insidiosum was very abundant in sewage-impacted areas. The tolerant and opportunistic species are favored after the summer due to the extra organic matter input. All community parameters showed lower values after the summer, and also a trend to diminish along the studied period.